Reducing Document Rejection Rate In Electronic Document Management System Workflow By E-Certification And Verification Stage - Rahmat, Rashitah (2020)
A study is conducted at a paperless ISO9001:2015 certified semiconductor manufacturing plant to improve document approval workflow. Interlinked floor automation systems run the manufacturing line. Online systems such as manufacturing execution system, statistical process control and recipe management systems have parameters and settings extracted from data in electronic document management system (DMS) automatically upon document update. To ensure that products are delivered to customers on time, changes to specifications must be done and approved promptly. Rejected documents during approval workflow require documents to be revised and resubmitted for approval. This rework activity may prolong a document approval process. One of the factors that affect document rejection rate is wrongly written process parameters which cause failure in data extraction.This resulted in many processes on the manufacturing floor to be placed on hold, hence delaying committed delivery to customers. The objectives of this study are to identify factors that influence rejection of documents in the approval workflow, propose solutions to reduce number of documents rejected in the approval process and evaluate the effectiveness of these proposals. Scope of this study covers internal and external documents registered in the company which include policies, job descriptions, organization charts, specifications, technical reports and records. Two proposals to reduce document rejection rate are creating an online application called E-Cert and the introduction of verification step before the document approval workflow. In the first proposal, E-Cert, a 3-level electronic certification process for specification writers has been introduced to ensure that only certified writers could revise or edit any specifications. The new certification process was successfully implemented and the data has been closely monitored for the period of 6 months. In the second proposal, a verification stage is added prior to document revision submission in DMS to filter out any incorrectly written tool parameters and process settings. This verification stage is done for two types of documents: process related and statistical process control related. Data monitored after implementation showed document rejection rate based on wrongly written process parameters was reduced significantly. Document rejection rate for process category document reduced from 48.8% to 6.5% while for statistical process control category the rejection rate improved from 40.5% to 4.2%. Results obtained from both improvements done to DMS have reduced the document rejection rate in the approval process.